2021
DOI: 10.3758/s13415-021-00976-9
|View full text |Cite
|
Sign up to set email alerts
|

Post-error slowing in anxiety and obsessive-compulsive disorders

Abstract: Altered brain response to errors in anxiety and obsessive-compulsive disorders (OCD) suggests cognitive control abnormalities across both types of illness, but behavioral metrics of cognitive control function have yet to be compared in patients selected from these different diagnostic categories. Thus, we examined post-error slowing (PES), a behavioral adjustment that typically occurs after a mistake, in children and adolescents with and without a primary anxiety disorder (N = 103 anxiety and N = 28 healthy co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 102 publications
0
6
0
Order By: Relevance
“…Post error slowing is an increase in RT on the response following an incorrect response and can be used as a marker of cognitive control, as this process is thought to reflect the capacity to flexibly adjust behavior after an outcome (Dutilh, van Ravenzwaaij, et al, 2012;Dutilh, Vandekerckhove, et al, 2012). In non-sequential tasks, increased post error slowing (greater RTs following error trials) has been observed in ANX compared to both OCD and HCs (Rueppel et al, 2022). In the current experiment, increased post error slowing in response to errors at position 4 could give rise to increased RTs at position 1 and the appearance of an increased initiation cost in participants with ANX compared to HCs.…”
Section: Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…Post error slowing is an increase in RT on the response following an incorrect response and can be used as a marker of cognitive control, as this process is thought to reflect the capacity to flexibly adjust behavior after an outcome (Dutilh, van Ravenzwaaij, et al, 2012;Dutilh, Vandekerckhove, et al, 2012). In non-sequential tasks, increased post error slowing (greater RTs following error trials) has been observed in ANX compared to both OCD and HCs (Rueppel et al, 2022). In the current experiment, increased post error slowing in response to errors at position 4 could give rise to increased RTs at position 1 and the appearance of an increased initiation cost in participants with ANX compared to HCs.…”
Section: Groupmentioning
confidence: 99%
“…Post-error slowing has not often been studied in the context of OCD and the results are mixed, possibly because the phenomenon can be studied in the context of nearly any task and the specific task itself may play a role. One study used a flanker task with congruent and incongruent stimuli and showed deficits in posterror slowing in participants with OCD compared to HCs (Modirrousta, Meek, Sareen, & Enns, 2015), while another that used a stop-signal task did not observe a difference in participants with OCD, but did in patients with ANX (Rueppel, Mannella, Fitzgerald, & Schroder, 2022).…”
mentioning
confidence: 99%
“…Post-error slowing (PES) is a behavioral index of error monitoring, defined as the slowing of response time on a post-error trial. While different accounts explain the PES phenomenon (Danielmeier & Ullsperger, 2011;Dutilh et al, 2012;Rueppel, Mannella, Fitzgerald, & Schroder, 2022), PES generally reflects the behavior adjustment mechanism following error-making and serves as a measure of cognitive control. Both SAT and PES capture individuals' 'strategy' during task performance.…”
mentioning
confidence: 99%
“…Also, children are slower and commit more errors compared to adults (e.g., Santesso, Segalowitz, & Schmidt, 2006; for a review, see Hämmerer, Müller, & Li, 2014). There are mixed findings considering PES in childhood (Rueppel et al, 2022). Some studies find no age-related changes in PES (Denervaud et al, 2021;Ladouceur et al, 2007;Taylor, Visser, Fueggle, Bellgrove, & Fox, 2018), some studies report a developmental decrease in PES (Meyer, Weinberg, Klein, & Hajcak, 2012;Smulders, Soetens, & van der Molen, 2016) and others find a developmental increase in PES (Hogan, Vargha-Khadem, Kirkham, & Baldeweg, 2005;Overbye et al, 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation